IMPLEMENTASI MODUL PROJECT BASED LEARNING PADA PEMBELAJARAN EKSPRESI DIRI MELALUI HOBI DI KELAS V SEKOLAH DASAR - Ade Irmawati; Priska Amalia Sipayung2; Zia Melana Tasya; Dwi Novita Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Indonesian language learning in the Merdeka Curriculum emphasizes literacy development, critical reasoning, and the ability to express ideas and feelings contextually. One effective approach to support these goals is the implementation of Project Based Learning (PjBL) modules. This study aims to describe the implementation of an Indonesian language learning module on the topic Self-Expression through Hobbies in grade V elementary school and to examine its contribution to students’ engagement and language skills. This research employed a qualitative descriptive approach involving fifth-grade students as participants. Data were collected through classroom observation, documentation analysis, and examination of students’ learning products. The findings reveal that the PjBL-based module enhances students’ active participation, strengthens listening, speaking, reading, and writing skills, and encourages students to express ideas and experiences in a structured and creative manner. The study concludes that project-based Indonesian language learning modules effectively support meaningful and contextual learning in elementary education.